Assessment of insulin action on carbohydrate metabolism: physiological and non‐physiological methods. Issue 6 (19th May 2013) - Dube, S.; Errazuriz, I.; Cobelli, C.; Basu, R.; Basu, A.
Abstract Carbohydrate metabolism in humans is regulated by insulin secretion from pancreatic β‐cells and glucose disposal by insulin‐sensitive tissues. Insulin facilitates glucose utilization in peripheral tissues and suppresses hepatic glucose production. Any defects in insulin action predispose an individual to glucose intolerance and Type 2 diabetes mellitus. Early detection of defects in insulin action could provide opportunities to prevent or delay progression of the disease state. There are different approaches to assess insulin action. Initial methods, such as peripheral insulin concentration and simple indices, have several limitations. Subsequently, researchers developed methodologies using intravenous glucose infusion to determine glucose fluxes. However, these methodologies are limited by being non‐physiological. Newer, innovative techniques that have been developed are more sophisticated and physiological. By modelling glucose kinetics using isotope dilution techniques, several robust parameters can be obtained that are physiologically relevant and sound. This brief review summarizes most of the non‐physiological and physiological methodologies used to measure the variables of insulin action.